MDGC-MS analysis of essential oils from Protium heptaphyllum (Aubl.) and their antifungal activity against Candida specie - M. MOBIN; S.G. DE LIMA; L.T.G. ALMEIDA; J.P. TAKAHASHI; J.B. TELES; M.W. SZESZS; M.A. MARTINS; A.A. CARVALHO; M.S.C. MELHEM
ABSTRACT Protium heptaphyllum is found in the Amazon region, and in various Brazilian states and South American countries. Also Known as almecega, it produces an oil resin used in traditional medicine as analgesic, anti-inflammatory, cicatrizant and expectorant, it is rich in pentacyclic triterpenes and essential oil. The main objective of this study was to analyze the chemical composition of P. heptaphyllumresin (OEPh) over different extraction times and to evaluate their antifungal activity against Candida species, obtained from gardeners with onychomycosis, using the disk diffusion method. The OEPh was obtained by hydrodistillation and analyzed by Multidimensional Gas Chromatography coupled with Mass Spectrometry (MDGC / MS). Candida species were obtained from lesions on the nails of horticulturist from a community garden in the city of Teresina, Piauí, Brazil. The antifungal activity in concentrations of 1000 µg/L, 500 µg/L and 250 µg/L, PROTOCOL M44-A2 (CLSI 2009) OEPh was tested. The main constituents identified were: l-limonene, α-terpineol, p-cineol, o-cymene and α-phellandrene, however, its composition varies significantly with extraction time. All species, except C. rugosa, were inhibited with halo (≥ 14 mm) at 1000 μg / L. C. krusei is naturally resistant to the drug fluconazole, but when tested with OEPh the clinical species (case 9) demonstrated sensitivity in three dilutions (halo ≤ 10 ≥ 14) and the standard strain was inhibited at concentration of 1000 μg/Lg / L (halo 14mm). A similar situation also occurred with the standard strain of C. parapsilosis (halo ≥ 11mm). OEPh has considerable antifungal activity, which merits further investigation for alternative clinical applications, since this species is widely distributed in our community, and it presents good yields, and also has important therapeutic applications.